Cinética de maturação nuclear e fecundação in vitro de oócitos bovinos imaturos injetados em folículo pré ovulatório - Simões, Luiz Manoel Souza (2017)
The production of bovine embryos can be performed by in vivo and in vitro biotechniques. In in vivo embryo production, ovarian superstimulation is used to promote multiple ovulations. For this purpose, ovarian superstimulation protocols were developed. However, embryo donor cows are subjected to several manipulations and hormonal stress during superovulation and embryo collection procedures. In addition, some cows do not respond to superovulation protocols. Such difficulties in the in vivo embryo production are not observed in the in vitro technique, that consists in performing, via in vitro, the maturation and fecundation of the oocytes and initial culture of the embryonic development. However, embryos produced in vivo have superior quality when compared to those produced in vitro, which leads to greater cryotolerance and better pregnancy results. Thus, an alternative to improve embryo quality and to avoid the difficulties of in vivo production is the use of intrafollicular oocyte injection technique (IFOI). However, the production of embryos by this technique is still low and variable among cows. Thus, the objective of the study was to verify if the process of in vivo maturation of several oocytes in pre ovulatory follicle is related to a low production of embryos by the IFOI technique. For this purpose, two experiments were performed to evaluate maturation kinetics (Experiment 1) and in vitro fecundation (Experiment 2) of oocytes matured in pre ovulatory follicle after IFOI. It was found that the maturation of oocytes in the pre ovulatory follicle for 20 hours does not alter maturation kinetics and increases in vitro fertilization capacity in relation to oocytes that were matured in vitro. Therefore, the maturation of several oocytes in the preovulatory follicle is not the determining factor for low embryo production by the IFOI technique.